Material and Technique Analysis of Qing Dynasty Official Style Architectural Polychrome Paintings in Hangzhou, Zhejiang, China - Ling Shen; Dan Hua; Baisu Nan; Yao Yao; Hong Duan; Jiakun Wang (Crystals)
Hangzhou was the political and economic center of the Southern Song Dynasty (1127–1279 AD) and also the southern end of the Beijing-Hangzhou Grand Canal during the Ming and Qing Dynasties (1368–1644 AD). This historical position allowed the city’s economy to develop rapidly and influenced the form of its polychrome paintings with the imperial official style of the north China. However, due to the high temperature and rainy natural preservation conditions, southern polychrome paintings have always been a weak link in Chinese architectural polychrome painting craftsmanship. This study focuses on two well-preserved official-style architectural polychrome paintings in the grand halls from the late Qing period in Hangzhou. Through multi-techniques such as optical microscopy (OM), scanning electron microprobe with energy dispersive X-ray spectroscopy analysis (SEM-EDX), micro-Raman spectroscopy, micro-Fourier Transform Infrared spectroscopy (μ-FTIR), and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS), it was found that there is a significant difference from the reported common non-ground architectural paintings in the south, typically having four-layer structures with a white base and ground plaster layer in preparation for painting. The appearance of pigments such as artificial ultramarine (Na6Al4Si6S4O20) and emerald green (Cu(C2H3O2)2·3Cu(AsO2)2) indicates that the paintings were made at least after the 1830s, and the use of malachite green dye and copper phthalocyanine blue (PB 15:X) suggests that unrecorded restorations were also performed after the 20th century. All samples are coated with a layer of alkyd resin, which may have been added during the repairs in the latter half of the 20th century, leading to the black discoloration of the present paintings, especially in areas where emerald green was used. This study provides an important case for the study of the official style of polychrome painting craftsmanship in the southern region of China and also offers important references for the future protection and restoration of traditional architectural polychrome painting.